Erinnerung und Identität: Literarische Konstruktionen in Doeschka Meijsings Prosa - Lammer, Christina (transcript, 2020)
The "mimesis of memory" and an intersectionally oriented narratology - memory and identity as central themes in Doeschka Meijsing's literary works